Uniwersytet i komercjalizacja. Rekonstrukcja zachodniej debaty - Melosik, Zbyszko (Wydawnictwo Naukowe Uniwersytetu im.Adama Mickiewicza w Poznaniu, 2012)
The article concerns the phenomenon of commercialization of the modern university, and especially its two primary functions: research and teaching. On one hand, the author analyzes such phenomena as the marketisation of academic knowledge, which becomes a “commodity for sale”, and scientists, because of the dependence of the big bussines are forced to give up their passion for seeking truth. On the other hand, the learning process is shown in the context of the prevailing reductionist phenomenon of “supermarketization”, where the student becomes the client and the university is transformed into a big department store.
University and Commercialization. Reconstruction of the Western Debate
Keywords: commercialization of the modern university; marketization of academic knowledge; “supermarketization”